Prevalence and clinical and prognostic value of “intact” coronary arteries in patients with acute coronary syndrome - O. L. Barbarash; E. S. Kartashyan; V. V. Kashtalap; S. A. Berns; V. I. Ganyukov; S. A. Evtushenko; V. Yu. Kheraskov; G. V. Moiseenkov; L. S. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To analyse retrospectively the prevalence and prognostic value of “intact” coronary arteries (CA) in patients with acute coronary syndrome (ACS). Material and methods. In 2006-2007, 913 urgent coronary angiographies were performed in ACS patients. The follow-up length was 12 months after hospital discharge. Results. No CA occlusion or stenosis was detected in 76 (8,3%) out of 913 ACS patients. The clinical group with “intact” CA mostly included individuals with non-Q myocardial infarction; the diagnosis was confirmed by biomarkers in 22%. The in-hospital and post-discharge prognosis was better, compared to the patients with atherosclerotic CA stenosis. In addition, gastro-intestinal pathology was more prevalent in individuals with “intact” CA. Conclusion. The study results confirm the possibility of coronary heart disease and ACS, in particular, in patients with “intact” CA. They also point to the importance of using all the available ACS criteria while identifying the causes of chest pain syndrome.